La macchina e le forme dell’azione: deficit fronetico e autonomia artificiale - Pisano, Aldo (Mechane, 2021)
Starting from the difference between “strong-Ai” and “weak-Ai”, this paper wants to underline the present and future questions coming out from the development of Artificial Intelligences and their collocation in the field of applied ethics. Firstly, the paper will focus on the present time, then on the ethical and juridical implications of weak-Ai uses. Secondly, it will go deeply into the ethical and anthropological matters, which come out from the possibility of a strong-Ai use. About the second issue, the work will underline the difference between human and machine’s act; in this sense, the machine probably has no skills in adapting its action to a particular moral situation (phronetic deficiency). That’s why it has to be considered as a sub-symbolic entity, out of the “world of meaning” where all ethical acts have a purpose and action’s motivations can be explained.